Organizaciòn administrativa contable y tributaria a la Empresa comercial Ivan Alexandher Torres Torres de la ciudad de Loja en el periodo 01 de enero al 30 de abril del 2014 - Sinchire Villalta, Cristian Rene (2016)
The thesis entitled "ADMINISTRATIVE ORGANIZATION AND TAX ACCOUNTING FOR COMMERCIAL COMPANY OF IVAN TORRES ALEXANDHER Loja in the period January 01 to 31 April 2014", was developed to implement a system of commercial accounting under International Standards (NIC) and according to the needs of the company to facilitate the control of their operations, thereby enabling maximum optimization of resources aimed at the enlargement of the company. Also known in an effective manner the economic situation will provide the financial statements for its owner to make the right decisions. He focused on the development of specific objectives where: administrative, accounting and tax organization was conducted by multiple features, starting with the lifting of the inventory that facilitated the better organization of commercial products for the fulfillment of economic and financial activity; in the same way they were designed and produced major books and records, developing a plan and manual accounts according to the needs of the company "Ivan Alexandher Torres Torres" and proceeded to record each transaction made by the company in the journal, ledger, balance sheet and financial statements of work which yielded information on the economic and financial situation of the company. The thesis concludes by demonstrating the need for tax accounting and administrative organization of the company, which through its application aimed at improving the administration of it, so that its owner is recommended to consider the thesis, for the same growth that will be a great contribution to the company.